Enhancing theoretical understanding of a practical biology course using active and self-directed learning strategies. Issue 2 (3rd April 2018) - Scott, Pamela H.; Veitch, Nicola J.; Gadegaard, Helen; Mughal, Muhammad; Norman, Gethin; Welsh, Michelle
Abstract: Laboratories are recognised as central in science education, allowing students to consolidate knowledge and master practical skills, however, their effectiveness has been questioned. Whilst laboratory practicals are useful for students' learning of basic procedures, they have been shown to be less effective for developing conceptual understanding of the subject. Interactive lectures and bespoke digital resources were utilised in order to enhance theoretical understanding of laboratory practical molecular sessions, thus enabling students to take responsibility for and direct their own learning, encouraging inquiry-based learning. Providing easy to access additional learning resources offered students an opportunity to better prepare themselves for the laboratory, and consolidate their knowledge through subsequent review and self-testing in their own time. Grades before and after implementation of these active learning strategies were analysed to look at the impact on student learning and this study demonstrates that integrating these into a challenging practical biology course improved grades significantly with a concomitant increase in the number of 'A' grades attained. Feedback to evaluate use and perceptions of both interactive lectures and digital resources were also analysed. It has been shown here that these activities enhanced student experience and understanding of the course.